1999
DOI: 10.1007/s001250051257
|View full text |Cite
|
Sign up to set email alerts
|

Early impairment of large artery structure and function in Type I diabetes mellitus

Abstract: Diabetes mellitus is associated with an increased risk of atherosclerosis [1]. Atherosclerosis is responsible for the increased rate of coronary heart disease, cerebrovascular disease and peripheral artery disease typical of diabetes mellitus [2±13]. It is not, however, well established how early alterations in large artery function, that may preceed the appearance and favour the progression of atherosclerotic lesions, i. e. a reduced arterial distensibility, occur in diabetic patients [14±16]. This is because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
79
1
14

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 45 publications
9
79
1
14
Order By: Relevance
“…4,5 Peripheral muscular arteries have been less well studied: results are variable, showing either unchanged brachial artery or increased radial artery stiffness in type 1 diabetes patients of mixed gender 21,22 or unchanged femoral artery stiffness in both males and females. 23 The behaviour of the brachial artery wall is of specific interest since it is often used as a model artery in the study of the endothelium, where dysfunction is suggested to precede atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Peripheral muscular arteries have been less well studied: results are variable, showing either unchanged brachial artery or increased radial artery stiffness in type 1 diabetes patients of mixed gender 21,22 or unchanged femoral artery stiffness in both males and females. 23 The behaviour of the brachial artery wall is of specific interest since it is often used as a model artery in the study of the endothelium, where dysfunction is suggested to precede atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…28 On the other hand, cross-sectional studies in DM-1 suggest that impaired autonomic nervous function occurs considerably earlier than, and therefore may contribute to, increased arterial stiffness. 6,7,9,10 Clearly, prospective studies are required to resolve this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have addressed some combinations of early changes, 8,10,13,14 but not extensively. We hypothesized that incipient neuropathy could influence large artery stiffness by direct effects on large arteries (through effects on tone, on proliferation of smooth muscle cells, and on extracellular matrix composition), as well as by effects on small arteries and arterioles, which might alter pulse wave reflection.…”
mentioning
confidence: 99%
“…Pulse pressure increases with age as a result of arterial stiffening. As compared with age-matched, non-diabetic controls, patients with type 1 diabetes have stiffer arteries, and the process of arterial stiffening is initiated before any signs of microvascular or macrovascular disease can be detected [61]. The increase in stiffness is correlated with duration of disease, independently of age [62], and this may be of particular importance in childhood-onset diabetes.…”
Section: Atherosclerosis Is Earlier and More Severe In Type 1 Diabetesmentioning
confidence: 99%